Relative rate coefficient measurements of OH radical reactions with (Z)-2-hexen-1-ol and (E)-3-hexen-1-ol under simulated atmospheric conditions - Peirone, Silvina Anahí (2014)
The relative rate technique was used to determine the rate coefficients of the reactions of OH radicals with (Z)-2-hexen-1-ol (k1), and (E)-3-hexen-1-ol (k2), at (296 ± 2) K and (750 ± 10) Torr of N2 or pure air. The reactions were investigated using a 200 L Teflon reaction chamber and a gas chromatograph coupled with flame-ionization detection. The following rate coefficients were derived, in units of cm3 mol−1 s−1: k1 = (1.1 ± 0.4) × 10−10 and k2 = (0.8 ± 0.1) × 10−10. This is the first experimental determination of k1 and k2. A comparison between the experimental rate coefficients (kexp) and the calculated rate coefficients using the structure–activity relationship (SAR) method (kSAR), for the reaction of different unsaturated alcohols with OH radicals is presented. The atmospheric lifetimes of the studied alcohols were estimated considering the rate coefficients of their reactions with OH and NO3 radicals. The radiative efficiencies (REs) were obtained from the infrared spectra of the two hexenols and the global warming potentials (GWPs) were then estimated. Atmospheric implications of the alcohols emission are briefly discussed.